Teori Kodifikasi Mushaf Usmani Telaah Kritis Atas Karya Régis Blachère - Andar Nubowo (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2014)
This article analyzes three Régis Blachère’s major theses pertaining to codification and promulgation of Mushaf ‘Utsmani (Utsmanic Manuscript) based on the assumption that codification of the Quranic texts is a historical event that needs to be examined through internal and external historicism approach. This articel argues that Blachère’s arguments about the political motives behind the codification of Mushaf ‘Utsmani is not based on a solid historical argument: his fault in presenting historical chronology of the codification of the Qur’an, his weakness in combining or compromising (talfiq) conflicting historical naratives, as well as his unobjetive in examining sources that he refers to. Therefore, the idea to reconstruct the critical edition of the Qur’an—which is influenced by Blachère theses, is hard to accomplish due to the absence of other authentic sources subsequent to abolition of non- Utsmanic Manuscripts. Keywords: the Qur’an, codification, Utsmanic Manuscript, Exegesis.